IMPLEMENTASI PERATURAN DAERAH NOMOR 8 TAHUN 2010 TENTANG PAJAK DAERAH DI KABUPATEN SAMBAS MENGENAI PAJAK USAHA SARANG BURUNG WALET DI KECAMATAN TELUK KERAMAT - Jerry Sumijan E.21111103 (FISIP Universitas Tanjungpura, 2013)
Writing this article aims to find out the local regulations implementing number 8 in 2012 on local taxes on business tax swiftlet in Sambas district . This study was included in the descriptive study with a qualitative analysis focusing on the locus of policy studies on : ( 1 ) the weak side regulation , ( 2 ) Factors that cause employers do not pay taxes bird's nest . The results of research in the field shows the span of 3 years after the Regional Regulation No. 8 of 2010 was published and determined , acceptance and / or local tax revenues from the business sector birds' nests yet to be realized due to hit problems with both the management and operation permits bird nest . Local Government faced with the fact that many businesses that abuse the building permit for the allotment of license management and utilization of bird's nest and the pros and cons in the community with the presence of bird's nest business on the environment and contribute to society . Building permit ignored because this study was not to examine the suitability of the Building Permit effort , but on the management and operation of bird's nest . Thus , although the building permit is not a permit swallow nest , but due to the location of the bird's nest there , then apply the Regional Regulation No. 8 of 2010 on Local Taxes in this particular Tax Swallow's Nest in Sambas district . It is hoped that future governments more assertive in terms of building permits to people not to arbitrarily abusing merely building for the management of bird's nest. Keywords; ImplementationRegulationsSwallowarea, the weaksideareas Regulations, employers Cause Not PayTaxes